Lingual Artery as the Recipient Vessel of Choice in Patients Requiring a Second or Third Free Flap in Recurrent Oral Cancers and Vessel-Depleted Neck: A 5-Year Experience in a Single Institute - Rajendra Dhondge; Mohsina Hussain; Archana Singh; Raj Nagarkar (Indian Journal of Plastic Surgery)
Introduction Reconstruction with free flaps becomes a challenge in recurrent cases having previously treated necks, in patients who have received prior radiation therapy or chemotherapy or both, and where the patient has already undergone free flap reconstruction in a prior surgery. Depleted cervical recipient vessels can increase the complexity of reconstruction in achieving successful free flap prefusion and thereby increasing flap thrombosis and eventually failure.